Social Reintegration and Rehabilitation of Obstetric Fistula Patients Before and After Repair in Sub-Saharan Africa: A Systematic Review - Shallon, Atuhaire; Ojengbede, Oladosu A.; Mugisha, John Francis; Odukogbe, Akin-Tunde A. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Social reintegration and rehabilitation of obstetric fistula patients before and after repair enhance their overall status, which may be unattainable even with a successful repair. Nonetheless, there is little traceable documentation about it even with supportive programs and projects, the thrust of this study. Methods: This is a systematic review involving a search of relevant literature from PubMed, Google scholar, PsychINFO, African Journals Online, Australian Journals Online, and open access journals of international organizations such as WHO, UNFPA, USAID, Engender Health, Fistula Foundation and Fistula Care Plus published between 1978 to date. Of the 46 articles identified, 25 were suitable for achievement of this study’s purpose. Results:Sub-Saharan African countries have recognized the overall burden of obstetric fistula and have devised strategies for its holistic management. Most countries have National Obstetric Fistula Strategic Frameworks which emphasize multi-sectoral and multidisciplinary approaches other than medical paradigms. Social reintegration and rehabilitation have been done through the identification of individual patient’s need/s. Projects and programs aiming to combat obstetric fistula and restore patients’ self-worth and dignity are: Lamaneh Suisse, and Delta Survie in Mali, Dimol in Niger, Medecins Sans Frontieres (MSF) in Burundi, FORWARD in Nigeria and Sierra Leone, Handicap International in Benin Republic, Women For Africa in Ghana and Liberia, TERREWODE and CoRSU both in Uganda, Hamlin Fistula Ethiopia in Ethiopia, and others which cut across the region. Conclusions: Effective social reintegration and rehabilitation strategies are still inadequate in Sub-Saharan Africa due to lack of political commitment and inadequate outreach programs. Keywords: obstetric fistula, recto-vaginal fistula, rehabilitation, social reintegration, vesico-vaginal fistula.